Abundance of molecular triple ionization by double Auger decay. Issue 1 (December 2018) - Roos, A.; Eland, J.; Andersson, J.; Squibb, R.; Koulentianos, D.; Talaee, O.; Feifel, R.
Abstract Systematic measurements of electron emission following formation of single 1s or 2p core holes in molecules with C, O, F, Si, S and Cl atoms show that overall triple ionization can make up as much as 20% of the decay. The proportion of triple ionization is observed to follow a linear trend correlated to the number of available valence electrons on the atom bearing the initial core hole and on closest neighbouring atoms, where the interatomic distance is assumed to play a large role. The amounts of triple ionization (double Auger decay) after 1s or 2p core hole formation follow the same linear trend, which indicates that the hole identity is not a crucial determining factor in the number of electrons emitted. The observed linear trend for the percentage of double Auger decay follows a predictive line equation of the form DA = 0.415 · Nve + 5.46.